Management of Diabetes Mellitus in Patients with Chronic Kidney Disease: A Comprehensive Systematic Review - Aini, Nur; Nadia (The International Journal of Medical Science and Health Research, 2024)
Background: Managing CKD in diabetic patients entails addressing its complications and minimizing the risk of other associated conditions, such as cardiovascular disease. This study aims to serve a comprehensive systematic review on diabetes management in CKD patients in literatures of the last 10 years Methods: The review adhered to PRISMA 2020 standards and analyzed full-text English literature from 2014 to 2024. It excluded editorials, review papers from the same journal, and submissions lacking a DOI. Literature sources included PubMed, SagePub, SpringerLink, and Google Scholar. Result: A total of  500 articles were retrieved from online databases (PubMed, SagePub, SpringerLink and Google Scholar). After three rounds of screening, five articles directly relevant to the systematic review were selected for full-text reading and analysis. Conclusion: Chronic kidney disease (CKD) is a common and serious complication in individuals with diabetes. Management involves controlling hypertension and hyperglycemia, along with using ACE inhibitors like finerenone and SGLT2 inhibitors such as dapagliflozin, sotagliflozin, and bexagliflozin.